Impacto do desemprego e do gasto público com saúde sobre a taxa de mortalidade nos atendimentos do SUS - Menescal, Lucas de Paula Andrade (2020)
This dissertation is dedicated to deepening the studies on the relationship between macroeconomic conditions and the health situation in a society. In this case, the role of public spending on health was also analyzed, in order to highlight its impact on the quality of public health services in Brazil, since the Unified Health System (SUS) serves the largest portion of the population. To analyze the effect on the quality of public services, the Mortality Rate in hospitals that serve by SUS was used, provided by the Hospitalization Information System (SIH/DATASUS). As a proxy for public spending, the variables Health expenditure per capita and the percentage of Own Revenue applied to Health, made available by the Information System on Public Health Budgets (SIOPS), were used. For the macroeconomic conditions, the Balance of Formal Jobs, made available by the General Employment Registry (CAGED), was used, and for the socioeconomic aspects, the Population and Deaths from External Causes were considered. Theoretical motivation is part of the debate, still without consensus, on the impact of variations in economic activity on the different mortality rates and on the health conditions of the population, that is, whether the relationship is pro-cyclical or counter-cyclical. The methodology used is based on the analysis of a data panel for Brazil at the state level, for the period 2002-2017, specifying a model of fixed effects estimated by Generalized Least Squares. The results of this paper suggest significant impacts of macroeconomic conditions and public spending on health on the quality of care in the public sector, highlighting the essential role of budgetary linkage and the growth of public spending for SUS financing.